Ship Anchoring Management Process In Guide Services - Sutryani, Henni; Purnaningrarti, Indah; Octavitri, Yollanda; Kusharyanto, Kusharyanto (Jurnal Ekonomi, 2024)
The port is the first link and gateway in a logistics distribution between countries and islands. By using ports, logistics distribution becomes faster and more efficient than being done through flight paths which require relatively more expensive costs and require more land. The port will connect several modes of transportation and several parties involved in the logistics management of goods. Every form of entry and exit of goods through the port must follow the procedures and SOPs applicable within the area. One procedure that has an important influence is the regulation on the management of Ship Anchoring in a port. Ship Anchoring Management is an activity to regulate the traffic of ships that will unload and / or load in a port. The Ship Anchoring management process is also an important process that deserves attention because the process is a process that will connect directly the land, namely the port with the ocean, namely ships. All forms of bureaucracy will be carried out by supervisory officers, namely Syahbandar and port management. The bureaucracy involves official and legal complete information and information about goods or cargo to be transported or unloaded on ships or to ports. With the management of Ship Anchoring, of course, all guide service activities afterwards will be carried out systematically and regularly. The ship's docking management process on ships will also affect the loading and unloading time by stevedoring companies (PBM), warehousing rental time, and other costs in the form of operational loading and unloading activities. This study uses data analysis, namely the Analysis Hierarchi Process (AHP) with respondents in the form of informants from the Indonesian port of Tanjung Priok, related Syahbandar parties, field officers, and stevedoring company managers. With the AHP method, it will produce a priority scale of several problems found from collecting facts in the field. This study produces the most influential party of the problem of ship anchoring management in a ship that will dock at Tanjung Priok port, namely by the Tanjung Priok Port Syahbandar, while the factors that cause these problems are law enforcement factors and rules that apply when carrying out ship anchoring management at Tanjung Priok Port Jakarta.